Novel role of the IGF-1 receptor in endothelial function and repair: studies in endothelium-targeted IGF-1 receptor transgenic mice. - Imrie, H; Viswambharan, H; Sukumar, P; Abbas, A; Cubbon, R; Yuldasheva, N; Gage, M; Smith, J; Galloway, S; Skromna, A; Rashid, S; Futers, T; et al. (American Diabetes Association, 2012)
We recently demonstrated that reducing IGF-1 receptor (IGF-1R) numbers in the endothelium enhances nitric oxide (NO) bioavailability and endothelial cell insulin sensitivity. In the present report, we aimed to examine the effect of increasing IGF-1R on endothelial cell function and repair. To examine the effect of increasing IGF-1R in the endothelium, we generated mice overexpressing human IGF-1R in the endothelium (human IGF-1R endothelium-overexpressing mice [hIGFREO]) under direction of the Tie2 promoter enhancer. hIGFREO aorta had reduced basal NO bioavailability (percent constriction to N(G)-monomethyl-l-arginine [mean (SEM) wild type 106% (30%); hIGFREO 48% (10%)]; P < 0.05). Endothelial cells from hIGFREO had reduced insulin-stimulated endothelial NO synthase activation (mean [SEM] wild type 170% [25%], hIGFREO 58% [3%]; P = 0.04) and insulin-stimulated NO release (mean [SEM] wild type 4,500 AU [1,000], hIGFREO 1,500 AU [700]; P < 0.05). hIGFREO mice had enhanced endothelium regeneration after denuding arterial injury (mean [SEM] percent recovered area, wild type 57% [2%], hIGFREO 47% [5%]; P < 0.05) and enhanced endothelial cell migration in vitro. The IGF-1R, although reducing NO bioavailability, enhances in situ endothelium regeneration. Manipulating IGF-1R in the endothelium may be a useful strategy to treat disorders of vascular growth and repair.